Joint measurement of risk aversion, prudence and temperance - Ebert, Sebastian; Wiesen, Daniel (Bonn Econ Discussion Papers, 2010)
We propose a method to measure the intensity of risk aversion, prudence (downside risk aversion) and temperance (outer risk aversion) in experiments. Higher-order risk compensations are defined within the proper risk apportionment model of Eeckhoudt and Schlesinger [American Economic Review, 96 (2006) 280] that are elicited using a multiple price list format. This approach is not based on expected utility theory. In our experiment we find evidence for risk aversion, prudence and temperance. Women demand higher risk compensations for all orders. The highest compensation is demanded for taking downside risk, not for being (second order) risk-loving. This highlights the importance of prudence when considering economic decisions under risk. -- Decision making under risk ; laboratory experiment ; prudence ; risk aversion ; temperance ; gender differences
Keywords: Arbeitspapier; Graue Literatur